Influence of Water Saturation, Grain Size of Quartz Sand and Hydrate-Former on the Gas Hydrate Formation - Yulia Zaripova; Vladimir Yarkovoi; Mikhail Varfolomeev; Rail Kadyrov; Andrey Stoporev (Energies, 2021)
The development of technologies for the accelerated formation or decomposition of gas hydrates is an urgent topic. This will make it possible to utilize a gas, including associated petroleum one, into a hydrate state for its further use or to produce natural gas from hydrate-saturated sediments. In this work, the effect of water content in wide range (0.7–50 mass%) and the size of quartz sand particles (porous medium; <50 μm, 125–160 μm and unsifted sand) on the formation of methane and methane-propane hydrates at close conditions (subcooling value) has been studied. High-pressure differential scanning calorimetry and X-ray computed tomography techniques were employed to analyze the hydrate formation process and pore sizes, respectively. The exponential growth of water to hydrate conversion with a decrease in the water content due to the rise of water–gas surface available for hydrate formation was revealed. Sieving the quartz sand resulted in a significant increase in water to hydrate conversion (59% for original sand compared to more than 90% for sieved sand). It was supposed that water suction due to the capillary forces influences both methane and methane-propane hydrates formation as well with latent hydrate forming up to 60% either without a detectable heat flow or during the ice melting. This emphasizes the importance of being developed for water–gas (ice–gas) interface to effectively transform water into the hydrate state. In any case, the ice melting (presence of thawing water) may allow a higher conversion degree. Varying the water content and the sand grain size allows to control the degree of water to hydrate conversion and subcooling achieved before the hydrate formation. Taking into account experimental error, the equilibrium conditions of hydrates formation do not change in all studied cases. The data obtained can be useful in developing a method for obtaining hydrates under static conditions.